EARTHQUAKE POTENTIAL IN BANDA ARC REGION BASED ON GEODETIC OBSERVATION - Rahmadani, Suchi
Eastern Indonesia is one of the most tectonically complex regions in the world, resulting from the convergence of four active plates: the Australian Plate, the Philippine Sea Plate, the Pacific Plate, and the Sunda Block. The Australian plate subducts in the southern part of Java to Seram Island and produces a subduction zone which then turns into a collision zone in the south of Timor Island to Seram Island. This collision zone then forms an earthquake source called the Banda Arc. This study aims to model the earthquake potential of Banda Arc region based on the comparion between geodetic seismicity data analysis. The first stage in this research is GPS data processing. After that, deformation analysis was carried out which included GPS time-series analysis, the estimation of GPS velocity, strain rate analysis, and conversion of strain rate to geodetic moment rate which is divided into several seismogenic zones. The next stage is the analysis of seismicity parameters and calculation of the seismic moment rate in each seismogenic zone. Then in the final stage, an analysis of the ratio of geodetic and seismic moment rates is carried out as well as calculation of the moment rate deficit and analysis of potential earthquakes. GPS velocity fields show that the Banda Arc deformation is caused mainly by the crustal shortening resulting from the interaction of the Australian, Pacific and Philippine Sea plates. The crustal shortening is also illustrated by the contraction pattern of geodetic strain that dominates the Banda Arc area, except in the northeast around the Papuan Bird's Head. Areas with high strain rates have a significant history of seismicity, such as the Flores-Wetar Back Arc, Ambon-Seram, and the Bird's Head of New Guinea. Moreover, the ratio of the geodetic moment rate to the seismic moment rate Banda arc region range from 0.38 – 7.0; where the four out of five zones show moment deficit. This moment deficit may be related to the presence of aseismic deformation or strain accumulation, under-sampling of long-term earthquakes in the used earthquake catalog, or a combination of these factors. However, the value of the moment deficit in the seismogenic zone has implications for earthquake hazard in the Banda Arc area. The convertion results of the moment deficit into moment magnitude indicate earthquake potential which equivalent to Mw 7.7 – 8.1. These results are expected to be input into the process of earthquake disaster risk reduction in the Banda Arc area.